Neutron scattering instrumentation at low power reactors for science, engineering and education - Farhi E.; Mohamad Idris F.; Mohamed A.A.; Yazid H.B.; Jamro R.; Harun Al Rashid M.; Mohamed Zin M.R.B. (IOS Press, 2023)
We demonstrate that a suite of neutron scattering instruments can be installed on low power reactors from e.g. 0.1 to 1 MW thermal power, including a powder diffractometer, a Laue diffractometer, a neutron imaging station, and small angle scattering machine. For each of these instruments, we estimate the performance using Monte-Carlo ray-tracing simulations with McStas, propose a cost effective design, and a set of applications covering science, engineering and education. In addition, we suggest a few shielding solutions to minimize the background level. 2015 IOS Press and the authors. All rights reserved.